PEMANFAATAN PENGGUNAAN PUPUK ORGANIK CAIR WORTEL DALAM MENINGKATKAN PRODUKTIVITAS TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Rahmadina Rahmadina (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2019)
The tomato plant (Lycopersicum esculentum Mill.) Is a multipurpose horticultural plant that is very useful as a commodity for various human needs. This study aims to determine the benefits of applying liquid organic fertilizer to carrot waste which can increase the productivity of tomato plants (Lycopersicum esculentum Mill.). This research was conducted from April to August 2019. This research was conducted in the screen house of the johor housing complex, Medan City, North Sumatra. This research was conducted using a completely randomized design (CRD) using a solution concentration of A = 0% as a treatment control, B = 5%, treatment C = 10%, treatment D = 15%, and treatment E = 20%. The type of data in this research is quantitative data. Data analysis used the one way ANOVA analysis of variance test with 5% accuracy, and continued with Duncan's multiple range test (DMRT). The results showed that liquid organic fertilizer derived from carrot waste can increase the productivity of tomato plants by having a plant height, number of leaves, number of branches, number of flowers and number of fruits that grow well and this has a significant effect on the growth of tomato plants The highest concentration is in a solution of 5% and 15% concentration, where at a concentration of 5% there is the number of leaves, fruit, flowers, and plant height while at a concentration of 15% on the number of branches on the tomato plant.PEMANFAATAN PENGGUNAAN PUPUK ORGANIK CAIR WORTEL DALAM MENINGKATKAN PRODUKTIVITAS TANAMAN TOMAT (Lycopersicum esculentum Mill.)